IRF2 is required for development and functional maturation of human NK cells - Persyn, Eva; Wahlen, Sigrid; Kiekens, Laura; Van Loocke, Wouter; Siwe, Hannah; Van Ammel, Els; De Vos, Zenzi; Van Nieuwerburgh, Filip; Matthys, Patrick; Taghon, Tom; Vandekerckhove, Bart; Van Vlierberghe, Pieter; et al. (Frontiers in Immunology, 2022)
Natural killer (NK) cells are cytotoxic and cytokine-producing lymphocytes that play an important role in the first line of defense against malignant or virus-infected cells. A better understanding of the transcriptional regulation of human NK cell differentiation is crucial to improve the efficacy of NK cell-mediated immunotherapy for cancer treatment. Here, we studied the role of the transcription factor interferon regulatory factor (IRF) 2 in human NK cell differentiation by stable knockdown or overexpression in cord blood hematopoietic stem cells and investigated its effect on development and function of the NK cell progeny. IRF2 overexpression had limited effects in these processes, indicating that endogenous IRF2 expression levels are sufficient. However, IRF2 knockdown greatly reduced the cell numbers of all early differentiation stages, resulting in decimated NK cell numbers. This was not caused by increased apoptosis, but by decreased proliferation. Expression of IRF2 is also required for functional maturation of NK cells, as the remaining NK cells after silencing of IRF2 had a less mature phenotype and showed decreased cytotoxic potential, as well as a greatly reduced cytokine secretion. Thus, IRF2 plays an important role during development and functional maturation of human NK cells.